A multi-channel bioimpedance-based device for Vietnamese hand gesture recognition - Nhat-Minh Than; Son-Thuy Nguyen; Dang-Nguyen Huynh; Thao-Nguyen Tran; Nguyen-Khoa Le; Huu-Xuan Mai; Cao-Dang Le; Tan-Thi Pham; Quang-Linh Huynh; Trung-Hau Nguyen (Scientific Reports)
Abstract This study addresses the growing importance of hand gesture recognition across diverse fields, such as industry, education, and healthcare, targeting the often-neglected needs of the deaf and dumb community. The primary objective is to improve communication between individuals, thereby enhancing the overall quality of life, particularly in the context of advanced healthcare. This paper presents a novel approach for real-time hand gesture recognition using bio-impedance techniques. The developed device, powered by a Raspberry Pi and connected to electrodes for impedance data acquisition, employs an impedance chip for data collection. To categorize hand gestures, Convolutional Neuron Network (CNN), XGBoost, and Random Forest were used. The model successfully recognized up to nine distinct gestures, achieving an average accuracy of 97.24% across ten subjects using a subject-dependent strategy, showcasing the efficacy of the bioimpedance-based system in hand gesture recognition. The promising results lay a foundation for future developments in nonverbal communication between humans and machines as it contributes to the advancement of technology for the benefit of individuals with hearing impairments, addressing a critical social need.